(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Il problema del conflitto di interessi nel diritto ecclesiastico dell’Italia repubblicana. - 2. Conflitto di interessi e finanziamento pubblico delle religioni. - 3. L’ombra del conflitto di interessi che accompagna nel suo cammino l’«invenzione» dell’otto per mille. - 4. Note di discussione. Contradictions and unclarities of “otto per mille”: between public interest in an open pluralism and individual interests in the rigidity of the religious market ABSTRACT: Religion, like politics and economics, risks fueling various forms of conflict of interest in the State. The constitutional choice to affirm a pluralist (or open) laicità aims precisely at avoiding and contrasting potential conflicts of interest caused by religious influences. The contradictions and the unclarities detected by several voices about the "otto per mille" economic support system could be read as indicators that Italy failed to implement a management of the public interest which should guarantee the exclusion of favoritism towards individual interests. The original fault of "otto per mille" system lies in the negotiated nature of the legislation that provides for it; the choice of a bilateral source makes clear the will of the State to operate, for purposes of its political consolidation, a substantial connection with the specific interests of some religious denominations in the acquisition and preservation of advantageous positions. It is therefore hoped an unilateral work of reform by the State, in particular the repeal of the fascist legislation about admitted cults and the promulgation of a general law on religious freedom.